Nutritional and nutraceutical potential of rice bean (Vigna umbellata) –a legume with hidden potential - Katoch, Rajan; Sanadya, Sanjay Kumar; Pathania, Kiran; Chaudhary, H. K. (Frontiers in Nutrition, 2023)
In the recent years there has been paradigm shift in global agriculture for the exploration of different underutilized crops as future potential crops. Rice bean [Vigna umbellata (Thunb.) Ohwi and Ohashi] one of the lesser known pulses among Vigna species has gained attention during last decade as food and nutritional security crop. Rice bean seeds are well-balanced source of beneficial constituents such as protein, carbohydrates, minerals, vitamins, PUFAs and anti-oxidants for health benefits and combating malnourishment in human populations. In the present investigation, fifteen diverse rice bean genotypes from north-western Himalayan region were investigated for nutrient, anti-nutrient and nutraceutical traits. The CP content in rice bean genotypes ranged from 22.56%-25.97% with the highest content in genotype IC-548766. The same genotype revealed the highest in vitro protein digestibility (53.69%). The lipid content in rice bean genotypes ranged from 1.87% to 3.17% with the higher proportion of linolenic acid (32.56% to 38.54%) and linoleic acid (16.55% to 17.88%), which are nutritionally desirable PUFAs. Macro- and trace-minerals that are important as cofactors in various metabolic reactions were observed in significant proportions in different genotypes. The globulins (11.55% to 12.72%) followed by albumins (5.83% to 7.45%) constituted the major protein fraction. The range of total phenolics (1.56% to 2.01%), total tannins (1.00% to 1.44%), condensed tannins (0.56% to 0.84%), hydrolysable tannins (0.33% to 0.71%), trypsin inhibitor (25.27 to 37.98 mg/g), phytic acid (3.22 to 4.16 mg/g), lipoxygenase activity (846.53 to 1047.89 units/mg) and saponins (0.87 to 1.44 mg/100g) was observed in rice bean genotypes. The raffinose family oligosaccharides (RFOs) revealed variation in their content with raffinose (1.85% to 2.56%), stachyose (0.94% to 1.56%) and verbascose (0.87% to 1.23%). Different nutrients and anti-nutrients were observed in balanced proportion in genotype IC-548770. The genotype IC-548757 revealed lower proportion of anti-nutrients. Similarly, the genotype IC-548759 and IC-548757 revealed higher level of free radical scavenging activity indicating nutritional and nutraceutical superiority of these genotypes. Rice bean legume has the potential to support more sustainable and resilient food and nutritional security in future. Our study highlights potential of rice bean genotypes as functional ingredients for food and nutritional security.